The role of participation in sustainable community development programmes in the extractives industries - Catherine Macdonald (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2017)
A major challenge for almost all extractives activity is that benefits accrue predominantly at the national level while disruptions are invariably highly localized close to the resource. Recently, extractives companies have intensified efforts to correct this imbalance. The aim of this paper is to identify the optimal approach for companies to encouraging sustainable local development among host communities. The role that government and civil society actors can play in supporting this process is also addressed. Community participation is central to the discussion, which makes reference to case studies, particularly that of the community development programmes of a gold mine in Tanzania over a period of 15 years.
Keywords: Z1; Q3; Y8; Y9; 330; community development; community participation; sustainable development; extractives industry